2014
DOI: 10.5114/hpr.2014.46487
|View full text |Cite
|
Sign up to set email alerts
|

Sexual self-esteem and sexual needs of young adults with cerebral palsy

Abstract: Sexuality is an important part of human existence, irrespective of race, religion or level of physical fitness. It can, however, be treated and exhibited by individuals in very different ways. The place of sexuality in a person's life, and in the way it is materialised, is determined by a number of biopsychosocial factors. For some, the presence of these factors and their influence is not a matter of choice. They may arise as a consequence of the psychophysical condition of their organism. People with motor di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
(19 reference statements)
0
5
0
1
Order By: Relevance
“…Earlier analyses and their findings published in our report [12] enabled us to dichotomize respondents into two extreme, statistically significantly different subgroups based on the co-presence of high levels and low levels of sexual esteem and sexual needs, respectively. The survey based on the sexual needs questionnaire led to the creation of respondents’ profiles encompassing different aspects of human sexual needs—the existence of such needs, a desire for sexual interaction, preferred frequency of sexual interactions.…”
Section: Methodological Basis Of the Studymentioning
confidence: 90%
See 2 more Smart Citations
“…Earlier analyses and their findings published in our report [12] enabled us to dichotomize respondents into two extreme, statistically significantly different subgroups based on the co-presence of high levels and low levels of sexual esteem and sexual needs, respectively. The survey based on the sexual needs questionnaire led to the creation of respondents’ profiles encompassing different aspects of human sexual needs—the existence of such needs, a desire for sexual interaction, preferred frequency of sexual interactions.…”
Section: Methodological Basis Of the Studymentioning
confidence: 90%
“…Human sexuality is a complex issue that as well as being an important aspect of our functioning is also a scientific discipline encompassing the psychology of emotional and motivational processes, and part of the model approximating the regulation of human functioning. The self-image of one’s sex life (sexual esteem) and sexual needs that all people develop guide their actions in this intimate sphere of life [7, 12, 61, 62, 66, 72]. However, sexual esteem and sexual needs are not the only factors that influence sexual activity manifested through specific sexual behaviors [21, 26, 49]: their range includes also body performance and especially the level of physical fitness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stigma and misconceptions about the concepts of disability and sexuality of persons with albinism impact more, and negatively on young people with disabilities in Africa. Studies have reported that adolescents with disabilities feel socially isolated (Cheng and Udry 2002) and have low self-esteem and sexual self-esteem, especially girls with disabilities (Czapla and Otrębski 2014;Esmail, Darry, Walter and Knupp 2010;Hilberink et al 2013;Rueda, Linton and Williams 2014;Maart and Jelsma 2010;McKenzie and Swartz 2011;Yousafzai, Edwards, D'Allesandro and Lindström 2005). Young persons with disabilities, particularly girls, are more likely to be bullied (Eisenberg, Gower, McMorris and Bucchianeri 2015).…”
Section: A D I 236mentioning
confidence: 99%
“…However, differences were observed in the case of certain dimensions of the self-concept: sport, school and social competencies. Respondents from the clinical group assessed their potential in romantic relationships as lower, too (see Czapla & Otrębski, 2014).…”
Section: Introductionmentioning
confidence: 99%